Integrative emotion regulation: Process and development from a self-determination theory perspective. (August 2019) - Roth, Guy; Vansteenkiste, Maarten; Ryan, Richard M.
Abstract: Grounded in self-determination theory's (SDT; Ryan & Deci, 2017) organismic perspective, we present a process view of integrative emotion regulation. SDT describes three general types of emotion regulation: integrative emotion regulation, which focuses on emotions as carrying information that is brought to awareness; controlled emotion regulation, which is focused on diminishing emotions through avoidance, suppression, or enforced expression or reappraisal; and amotivated emotion regulation, in which emotions are uncontrolled or dysregulated. We review survey and experimental research contrasting these emotion regulation styles, providing evidence for the benefits of integrative emotion regulation for volitional functioning, personal well-being, and high-quality relationships, and for the costs of controlled emotion regulation and dysregulation. The development of emotion regulation styles is discussed, especially the role of autonomy-supportive parenting in fostering more integrative emotion regulation, and the role of controlling parenting in contributing to controlled or dysregulated emotion processing. Overall, integrative emotion regulation represents a beneficial style of processing emotions, which develops most effectively in a nonjudgmental and autonomy-supportive environment, an issue relevant to both development and psychotherapy.